(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2025)
Social media represents an essential communication technology in everyday life. Using social media as a learning medium can encourage the quality of learning by taking advantage of all the facilities for communicating and sharing information owned by the media for the educational process. At this time, after the COVID epidemic, social media has a great influence on a person’s life, with both positive and negative effects, especially for primary school students. This study was conducted to determine the impact of social media on the learning process of Tamil national-type school students (Sekolah Jenis Kebangsaan Tamil, SJKT) in Kedah. This study is a quantitative study using the survey method. The number of samples selected based on the criteria set is to have a smartphone. A total of 238 students were selected to answer the questionnaire distributed via Google Forms. The data obtained in this study were analyzed using descriptive statistical methods, namely frequency, percentage, and mean. The findings reveal that 72% of the students spend more than 3 hours daily on social media platforms such as WhatsApp, Facebook, Telegram, Instagram, and online games. Additionally, 65% of students admitted to prioritizing social media activities over academic tasks, significantly reducing their effective study time. Time for learning lessons becomes less effective because students spend a lot of time on social media. Lack of parental supervision at home also causes students to freely use media platforms for playing purposes. The researcher hopes that this research process can benefit various parties by encouraging them to take appropriate steps to improve the learning process of primary school students.